Effect of substrates to formulate Trichoderma harzianum based bio-fungicide in controlling seedling disease (Rhizoctonia solani) of brinjal (Bangladesh Journal of Agricultural Research, 2017)
Efficacy of three different substrates viz., rice bran, wheat bran, grass pea bran and their combinations with mustard oilcake (MOC) were tested to formulate a suitable Trichoderma harzianum based bio-fungicide for controlling seedling disease of brinjal caused by Rhizoctonia solani in tray soil as well as in seedbed soil under net house condition of Bangladesh Agricultural Research Institute (BARI), Gazipur during 2010 to 2014. The results of three years experiments revealed that T. harzianum bio-fungicides formulated in five different combinations of substrates viz., (1) rice bran + wheat bran, (2) rice bran + mustard oilcake (MOC) (3) rice bran + grasspea bran, (4) rice bran + wheat bran + MOC and (5) rice bran + grasspea bran +MOC were equally effective to control the soil borne seedling disease of brinjal caused by Rhizoctonia solani in tray soil and seedbed condition. In addition, vegetative growth of brinjal seedlings viz., shoot length, shoot weight, root length and root weight were enhanced significantly by the T. harzianum bio-fungicides in R. solani inoculated seedbed condition.Bangladesh J. Agril. Res. 42(1): 159-170, March 2017